Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

The functions below represent the amounts of water released from two reservoirs over [tex]x[/tex] weeks:

Reservoir A:
[tex]\[ f(x) = x^2 - 7x + 5 \][/tex]

Reservoir B:
[tex]\[ g(x) = 3x^2 - 6x + 2 \][/tex]

The function [tex]h(x) = f(x) - g(x)[/tex] represents the difference in the amounts of water released.

Determine which statements about [tex]h(x)[/tex] and about the reservoirs are true. Check all that apply.

A. [tex]h(x) = -2x^2 - 13x + 3[/tex]
B. [tex]h(x) = -2x^2 - x + 3[/tex]
C. Reservoir A releases less water than Reservoir B over 1 week.
D. Reservoir A releases the same amount of water as Reservoir B over 1 week.
E. Reservoir A releases more water than Reservoir B over 1 week.


Sagot :

Let's analyze the functions given for the released amounts of water from the two reservoirs.

Reservoir A:
[tex]\[ f(x) = x^2 - 7x + 5 \][/tex]

Reservoir B:
[tex]\[ g(x) = 3x^2 - 6x + 2 \][/tex]

The function representing the difference between the amounts of water released by the two reservoirs is:
[tex]\[ h(x) = f(x) - g(x) \][/tex]

First, let's find the expressions for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] when [tex]\( x = 1 \)[/tex] week:

For Reservoir A:
[tex]\[ f(1) = 1^2 - 7 \cdot 1 + 5 \][/tex]
[tex]\[ f(1) = 1 - 7 + 5 \][/tex]
[tex]\[ f(1) = -1 \][/tex]

For Reservoir B:
[tex]\[ g(1) = 3 \cdot 1^2 - 6 \cdot 1 + 2 \][/tex]
[tex]\[ g(1) = 3 - 6 + 2 \][/tex]
[tex]\[ g(1) = -1 \][/tex]

Now, let's calculate [tex]\( h(1) \)[/tex]:

[tex]\[ h(1) = f(1) - g(1) \][/tex]
[tex]\[ h(1) = -1 - (-1) \][/tex]
[tex]\[ h(1) = -1 + 1 \][/tex]
[tex]\[ h(1) = 0 \][/tex]

Given the results:
[tex]\[ f(1) = -1 \][/tex]
[tex]\[ g(1) = -1 \][/tex]
[tex]\[ h(1) = 0 \][/tex]

Let’s evaluate the given statements one-by-one:

1. [tex]\( h(x) = -2x^2 - 13x + 6 \)[/tex]:

Check if this is true for [tex]\( x = 1 \)[/tex]:
[tex]\[ h(1) = -2(1)^2 - 13(1) + 6 \][/tex]
[tex]\[ h(1) = -2 - 13 + 6 \][/tex]
[tex]\[ h(1) = -9 \neq 0 \][/tex]

The first statement is False.

2. [tex]\( h(x) = -2x^2 - x + 3 \)[/tex]:

Check if this is true for [tex]\( x = 1 \)[/tex]:
[tex]\[ h(1) = -2(1)^2 - 1(1) + 3 \][/tex]
[tex]\[ h(1) = -2 - 1 + 3 \][/tex]
[tex]\[ h(1) = 0 \][/tex]

The second statement is True.

3. Reservoir A releases less water than Reservoir B over 1 week.

Check if [tex]\( f(1) < g(1) \)[/tex]:
[tex]\[ f(1) = -1 \][/tex]
[tex]\[ g(1) = -1 \][/tex]
[tex]\[ -1 \not< -1 \][/tex]

This statement is False.

4. Reservoir A releases the same amount of water as Reservoir B over 1 week.

Check if [tex]\( f(1) = g(1) \)[/tex]:
[tex]\[ f(1) = -1 \][/tex]
[tex]\[ g(1) = -1 \][/tex]
[tex]\[ -1 = -1 \][/tex]

This statement is True.

5. Reservoir A releases more water than Reservoir B over 1 week.

Check if [tex]\( f(1) > g(1) \)[/tex]:
[tex]\[ f(1) = -1 \][/tex]
[tex]\[ g(1) = -1 \][/tex]
[tex]\[ -1 \not> -1 \][/tex]

This statement is False.

To summarize:
- [tex]\( h(x) = -2x^2 - 13x + 6 \)[/tex] is False.
- [tex]\( h(x) = -2x^2 - x + 3 \)[/tex] is True.
- Reservoir A releases less water than Reservoir B over 1 week is False.
- Reservoir A releases the same amount of water as Reservoir B over 1 week is True.
- Reservoir A releases more water than Reservoir B over 1 week is False.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.